Razvoj rokometa na mivki - Bon, Marta (Šport (Ljubljana), 2018)
The article presents beach handball, its expert and historical development until the present day, an analysis and a synthesis of available resources and literature as well as sheds light on its development possibilities. Basically, beach handball differs from handball in the structure of the playing ground and the rules, but essentially also in terms of philosophy, technique and tactics. The aspects of attractiveness, aesthetics of the body, fair play and fun are pronounced. This game has been developing fast in the world and its media coverage is intense. In some countries (e.g. Spain) it has also received scientific research attention. In Slovenia, compared to the intense global development, its organisational and expert development is strongly lagging behind. There were some quite spontaneous tournaments two decades ago, two national team activities (in 2002 and 2015) and 4 national championships (also in 2016 for younger age categories). There has not been any planned systematic approach to the development of beach handball yet. Based on the analysis and synthesis we propose to the Handball Federation of Slovenia a model of measures, particularly the following: active support to the project, establishment of a system of competitions, training for stakeholders, connections with the National Olympic Committee of Slovenia and universities as well as an appropriate communication plan for the scheduled activities.
Keywords: igre z žogo; razvoj; rokomet; rokomet na mivki; vsebina igre